Canadian hockey literature : a thematic study - Blake, Jason, 1972- (University of Toronto Press, 2010)
The first book to focus exclusively on hockey in print, Canadian Hockey Literature is an accessible work that challenges popular perceptions of a much-beloved national pastime.